Employing Laparoscopic Surgery for Endometriosis. (July 2014) - Afors, Karolina; Murtada, Rouba; Centini, Gabriele; Fernandes, Rodrigo; Meza, Carolina; Castellano, Jesus; Wattiez, Arnaud
Endometriosis is a chronic, multifactorial disease, which can impact significantly on a women's quality of life. It is associated with pelvic pain, dyspareunia and intestinal disorders, and can lead to infertility. The use of laparoscopic surgery in the management of endometriosis is well documented; however, the optimal management of women with deep infiltrating disease remains controversial. This review describes the different surgical strategies for the treatment of endometriosis.